Amiodarone in cardiac transplant waiting list patients with severe heart failure - N. N. Koloskova; V. N. Poptsov; G. M. Salikhova (Вестник трансплантологии и искусственных органов, 2017)
Heart transplantation is the «gold standard» of severe heart failure treatment. Sudden arrhythmic death is the leading cause of death among these patients. Amiodarone is the only antiarrhythmic drug with beneficial effect on survival of patients with end-stage heart failure. Given its long half-life, pre-transplant use of amiodarone has been extensively discussed focusing on divergent results regarding morbidity and mortality after heart transplantation. Its adverse clinical events after transplantation remain debatable. This review is aimed at evaluation of the impact of amiodarone pretransplant use on mortality and complications after heart transplantation.